Indoor composting of vine by-products to produce substrates for mushroom cultivation - Pardo, A.; Perona, M.A.; Pardo, J. (Spanish Journal of Agricultural Research, 2007)
This paper describes a new technique for producing high quality, low cost organic substrates for use in the cultivation of the most widely consumed edible mushroom, Agaricus bisporus (Lange) Imbach. With production, economic and environmental concerns in mind, the aim of this work was to provide fresh impetus to the edible fungus industry by introducing alternative materials to those traditionally used in substrate production: in this case waste products from grape growing and wine making (vine shoots, grape stalks and grape pomace). These were composted under controlled conditions. While no more biologically efficient than traditional compost, the agronomic assessment of the alternative indoor substrates (performed using different proportions of grape stalks and vine shoots as base materials and using two varieties of Agaricus bisporus) showed them to be economically viable (their use reduces costs) and environmentally advantageous (their use reduces the emission of volatile compounds).